Systematic Review of PBL–LMS Effects on Critical Thinking and Adversity Quotient in Elementary Education - Ari Limay Trisno Putra; Ibnu Imam Al Ayyubi; Namiyah Fitriani; Firda Noerzanah; Alamul Huda Almuzakky (Sekolah Tinggi Ilmu Tarbiyah Bustanul 'Ulum Lampung Tengah, 2026)
Despite the increasing emphasis on critical thinking skills and adversity quotient in elementary education, existing studies remain fragmented and lack comprehensive synthesis regarding the integration of instructional models and digital platforms. Specifically, the combination of Problem-Based Learning (PBL) and Learning Management Systems (LMS) has not been systematically examined within elementary mathematics contexts. This study aims to synthesize empirical evidence on the effectiveness of PBL integrated with LMS in enhancing students’ critical thinking skills and adversity quotient. This research employs a Systematic Literature Review (SLR) using structured stages: identification, screening, eligibility, and inclusion. A total of 16 peer-reviewed articles published between 2020 and 2025 were selected from Google Scholar and Scopus based on predefined criteria. The analysis focuses on research design, intervention characteristics, and learning outcomes. The findings indicate that PBL–LMS integration effectively promotes critical thinking through problem exploration, collaboration, and reflection. It also strengthens students’ adversity quotient by fostering persistence, adaptability, and resilience in learning challenges. Furthermore, its effectiveness is influenced by instructional design quality, digital facilitation, and task alignment with student characteristics. This study contributes a focused synthesis highlighting the dual impact of PBL–LMS integration on cognitive and non-cognitive development in elementary mathematics learning.